Multi-bridge graphs are anti-magic - Yu Bin Tai; Gek Ling Chia; Poh-Hwa Ong (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2022)
An anti-magic graph is a graph whose |E| edges can be labeled with the first |E| natural numbers such that each edge receives a distinct number and each vertex receives a distinct vertex sum which is obtained by taking the sum of the labels of all the edges incident to it. We prove that the multi-bridge graph is anti-magic.